(untitled) (Bangladesh Journal of Pharmacology, 2013)
The current study was designed to evaluate the hypolipidemic and renopro-tective effects of methanolic extract of powdered Canscora decussata whole plant in the diabetic rabbits. Thirty rabbits were divided into five groups having 6 animals each including normal and diabetic controls groups, the remaining groups received methanolic extract in 400 and 600 mg/kg doses and another group got pioglitazone (3 mg/kg) for 30 days. Serum levels of triglycerides, total cholesterol, LDL-cholesterol, HDL-cholesterol, albumin, globulin and total proteins were estimated by using commercially available kits. The results showed that extract significantly (p<0.01) decreased the raised parameters including triglyceride, total cholesterol and LDL-cholesterol, atherogenic index, Coronary risk index up to normal values compared to diabetic rabbits. However, it significantly increased HDL-cholesterol, albumin, globulin and total protein levels. Therefore, it is suggested that methanolic extract of C. decussata exerts hypolipidemic and renoprotective effects in the alloxan-induced diabetic rabbits.